Evaluation of methods for assigning causes of death from verbal autopsies in India - Benara, Sudhir K.; Sharma, Saurabh; Juneja, Atul; Nair, Saritha; Gulati, B. K.; Singh, Kh. Jitenkumar; Singh, Lucky; Yadav, Ved Prakash; Rao, Chalapati; Rao, M. Vishnu Vardhana (Frontiers in Big Data, 2023)
Background: Physician-coded verbal autopsy (PCVA) is the most widely used method to determine causes of death (COD) in countries where medical certification of death is low. Computer-coded verbal autopsy (CCVA), an alternative method to PCVA for assigning the COD is considered to be efficient and cost-effective. However, the performance of CCVA as compared to PCVA is yet to be established in the Indian context.We evaluated the performance of PCVA and three CCVA methods i.e., InterVA 5, InSilico and Tariff 2.0 on verbal autopsies done using the WHO 2016 VA tool on 2120 reference standard cases developed from five tertiary care hospitals of Delhi. PCVA methodology involved dual independent review with adjudication, where required. Metrics to assess performance were Cause Specific Mortality Fraction (CSMF), sensitivity, positive predictive value (PPV), CSMF Accuracy and Kappa statistic.In terms of the measures of the overall performance of COD assignment methods, for CSMF Accuracy, the PCVA method achieved the highest score of 0.79, followed by 0.67 for Tariff_2.0, 0.66 for Inter-VA and 0.62 for InSilicoVA. The PCVA method also achieved the highest agreement (57%) and Kappa scores (0.54). The PCVA method showed the highest sensitivity for 15 out of 20 causes of death. This is a provisional file, not the final typeset article Conclusion: Our study found that the PCVA method had the best performance out of all the four COD assignment methods that were tested in our study sample. In order to improve the performance of CCVA methods, multicentric studies with larger sample sizes need to be conducted using the WHO VA tool.